ЖАПОН ТІЛІНДЕГІ СЫПАЙЫЛЫҚ КАТЕГОРИЯЛАРЫ: «ӨЗІМ» ЖӘНЕ «ӨЗГЕ» ОППОЗИЦИЯСЫ - Қалықова, Г. Қ. (Journal of Oriental Studies, 2016)
В данной статье рассматриваются категории вежливости в японском языке. Автор статьи, исследуя этикет в японском языке, сделал анализ понятиям «свой и чужой» в японском этикете. This article considers the categories of politeness in Japanese. The author researching etiquette in Japanese made analysis of the concepts of "mine and others’" in Japanese language.